2017
DOI: 10.1111/cpf.12474
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of constant load verification testing to confirm VO2max attainment

Abstract: Although maximal oxygen uptake (VO max) has been measured for almost 100 years, it is unknown when 'true' VO max is attained. Primary (the VO plateau) and secondary criteria are used to confirm VO max incidence, but frequency of the VO plateau varies, and secondary criteria are relatively invalid. The verification test (VER) seems to elicit similar estimates of VO max versus the incremental value (INC), yet existing data are limited by small populations and use of inadequate criteria to confirm 'true' VO max. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
8
17
2
Order By: Relevance
“…The results of the present study partially agree with those of Astorino [20]. Study number two in the Astorino [20] paper found a significant test x gender interaction where the males had a higher VO 2max on the incremental test compared to the supramaximal VP and the females did not. Conversely, study number one showed no test x gender effect but overall showed a significantly higher VO 2max in the incremental compared to the VP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the present study partially agree with those of Astorino [20]. Study number two in the Astorino [20] paper found a significant test x gender interaction where the males had a higher VO 2max on the incremental test compared to the supramaximal VP and the females did not. Conversely, study number one showed no test x gender effect but overall showed a significantly higher VO 2max in the incremental compared to the VP.…”
Section: Discussionsupporting
confidence: 91%
“…Some individuals may reach exhaustion in less than 2 min during supramaximal VPs, which may not be enough time to elicit VO 2max [19]. A recent study using data from 109 subjects found supramaximal VPs to elicit a significantly lower mean VO 2max compared to the GXT [20]. Theoretically, any work rate that falls in the severe domain should lead to exhaustion with VO 2max attainment [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in this study, VerT was conducted after only 8 minutes of active recovery (ie, 30% peak work rate) and carry over fatigue from GXT may explain the results. Recent studies showed a tendency of the less fit subjects to increase more trueV˙normalO2 during the VerT. However, in our data the magnitude of trueV˙normalO2 increase during VerT above GXT was not related to the absolute normalV˙O2max of the individual (Bland‐Altman correlation R = −0.07; Figure ).…”
Section: Perspectivecontrasting
confidence: 83%
“…This bias is lower than the one reported by Bhammar et al, (ie, 118 mLO 2 ·min −1 ) but higher than Sawyer et al, (ie, 40 mLO 2 ·min −1 ). Astorino and DeRevere in active young adults reported negative bias (−54 and −41 mL·min −1 ), indicating that VerT could underestimate GXT normalV˙O2max . Nevertheless, in this study, VerT was conducted after only 8 minutes of active recovery (ie, 30% peak work rate) and carry over fatigue from GXT may explain the results.…”
Section: Perspectivecontrasting
confidence: 52%
“…First, in contrast to many authors we chose a verification bout with supra-peak load, because using a submaximal load [30][31][32] do not correspond to the idea that a _ VO 2 -plateau can be provoked by a verification bout, as previously highlighted [3,8]. Second, many previous authors [20,30,[32][33][34] compared the verification-_ VO 2 and ramp-_ VO 2 on a group level and concluded that the verification was successful because there were no significant differences on a group level between the two _ VO 2 values. Obviously not group averages need to be compared with each other, but the two _ VO 2 values from each subject to define for each individual if _ VO 2 max was verified.…”
Section: Plos Onementioning
confidence: 99%